Status Al-Quran Digital dari Perspektif Fiqh - Khairul Anuar bin Mohamad; Mushaddad Hasbullah (Universiti Sains Islam Malaysia, 2024)
The working paper entitles ''The status of Quranic Digital from Fiqh Perspective''. There is no doubt taht in recent years, IT has been widely used in all aspect especially in our daily life. Our religion also accepts IT as one of the way to preach and it also has been widely used in Islamic world. One of the proof was the invention of Quranic Digital. Islamic technocrats have invented the Digital Quran for Muslim to make good use of it but also to help us to draw closer to Allah. The objective of this paper is to identify and explain about the fiqh's problems between Digital Quran and physical Quran such as Mushaf. This explanation hopefully can help Muslims to have confidence when using the Quranic-Digital especially in the mainstream. A research has been conducted to study about the fiqh's problem in Quranic Digital and the author found out that the Quranic Digital can be touch even without wudhu' or during period (Haidh) because of it was not physically written like Mushaf and the words was stored in the device with other equipment.